Improving Legal Protection for Children as Victims of Violence in Indonesia: A Review under the Child Protection Law - Shabika Ymani Maulana (Proceedings Series on Social Sciences & Humanities, 2023)
Children are a vulnerable group and too often become victims of violence in various forms, including physical violence, sexual violence, psychological violence, and child exploitation. The problems that arise when a child experiences physical, psychological, or sexual violence that impacts mental health cannot legally prosecute the perpetrator because only articles related to physical violence or visible physical injury apply, with no provisions regarding sanctions for the psychological impact experienced by the victim. The purpose of this study is to analyze the existing legal protection system in Indonesia and identify the weaknesses and challenges faced in protecting children as victims of violence. The research method used is a literature study by analyzing laws, regulations, and literature related to child protection in Indonesia. The results show that Indonesia has a relatively complete legal framework in protecting children as victims of violence. Important child protection laws, such as the Child Protection Act and the Anti-Trafficking Act, have been enacted. In addition, there are institutions and mechanisms responsible for handling cases of violence against children, such as the Indonesian Child Protection Commission (KPAI) and the Women and Children Protection Unit (PPA) in the police. Suggestions are expected to provide a better understanding of the efforts and forms of legal protection for children as victims of violence in Indonesia. By raising awareness and making the necessary improvements, it is hoped that children who are victims of violence can get better protection and have a brighter future.